2010
DOI: 10.1099/mic.0.039438-0
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter jejuni proteins Cj0952c and Cj0951c affect chemotactic behaviour towards formic acid and are important for invasion of host cells

Abstract: Campylobacter jejuni, an important food-borne bacterial pathogen in industrialized countries and in the developing world, is one of the major causes of bacterial diarrhoea. To identify genes which are important for the invasion of host cells by the pathogen, we screened altogether 660 clones of a transposon-generated mutant library based on the clinical C. jejuni isolate B2. Thereby, we identified a clone with a transposon insertion in gene cj0952c. As in the well-characterized C. jejuni strain NCTC 11168, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
88
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(94 citation statements)
references
References 42 publications
6
88
0
Order By: Relevance
“…Tlp7 belongs to the group A receptors if encoded by one single gene (cjj81176-0975) as in the reference strains 81-176 and 81116. But in the C. jejuni strains NCTC 11168 and B2, the sections for periplasmic binding and transmembrane localization are encoded on gene cj0952c, whereas the signalling domain is encoded by the adjacent gene cj0951c [30,77]. Thus, the membrane-associated partial receptor encoded by cj0952 (termed Tlp7 m ) belongs like the cjj81176-0975-encoded receptor, consisting of the membrane-associated and the cytoplasmatic domains (termed Tlp7 mc ), to group A, whereas the cytoplasmic part, encoded by cj0951c (Tlp7 c ), should be considered as group C chemoreceptor.…”
Section: Specific Campylobacter Chemoreceptorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Tlp7 belongs to the group A receptors if encoded by one single gene (cjj81176-0975) as in the reference strains 81-176 and 81116. But in the C. jejuni strains NCTC 11168 and B2, the sections for periplasmic binding and transmembrane localization are encoded on gene cj0952c, whereas the signalling domain is encoded by the adjacent gene cj0951c [30,77]. Thus, the membrane-associated partial receptor encoded by cj0952 (termed Tlp7 m ) belongs like the cjj81176-0975-encoded receptor, consisting of the membrane-associated and the cytoplasmatic domains (termed Tlp7 mc ), to group A, whereas the cytoplasmic part, encoded by cj0951c (Tlp7 c ), should be considered as group C chemoreceptor.…”
Section: Specific Campylobacter Chemoreceptorsmentioning
confidence: 99%
“…2. Domain organization of the three different C. jejuni Tlp-chemoreceptor groups: group A receptors are anchored by membrane-spanning regions in the inner and obviously also in the outer membrane, have a periplasmic sensory and a cytoplasmic signalling domain; the only group B receptor Tlp9 (CetA), anchored in the inner membrane, interacts with CetB triggering pyruvate and fumarate signals [84]; group C chemoreceptors consist of a single cytoplasmic signalling domain; the cytoplasmic Tlp7c (encoded by cj0951c) receptor is assigned to group C, while it was shown that there is no read-through mechanism [77], whereas the membrane associated forms Tlp7 m (encoded by cj0952c) and Tlp7 mc (encoded by cjj81176-0975 according to the nomenclature of the 81-176 sequence) are assigned to group A (depiction modified after Marchant et al [30]) lipid bilayers containing a defined number of chemoreceptors, allowed to characterize the interaction of chemoreceptors with regard to ligand binding, transmembrane signalling and activation of the chemotaxis histidine kinase CheA(Y). Thereby, it has been demonstrated that dimers of receptors are capable of binding ligands and to perform transmembrane signalling.…”
Section: Specific Campylobacter Chemoreceptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Altogether, it is difficult to identify chemoreceptors specific for a certain taxin, because the different MCPs can compensate each other in many cases, Thus, knockout mutants of chemoreceptor genes show often no defects in their phenotype (Vegge et al, 2009;Tareen et al 2010). Up to now, four chemoreceptor specificities are identified for Salmonella spp.…”
Section: Specific Salmonella Chemoreceptorsmentioning
confidence: 99%